Hemodynamic Modeling of Branch Retinal Artery Occlusion Involving Asymmetric Vascular Stenosis - Basuki Widodo; Ni Putu Dewi; Yuni Muarifadila; Annisa Sulistyaningtyasa; Arif Fatahillah; Tri Rahayuningsih (Jambura Journal of Biomathematics (JJBM), 2026)
The narrowing of retinal blood vessels, especially in conditions involving branch retinal artery occlusion (BRAO), can cause gradual and painless vision deterioration. Such vascular obstruction is also a contributing factor to eye stroke. This study investigates the influence of three asymmetric stenosis geometries, namely Bell--Cosine, Cosine--Overlapping, and Bell--Overlapping, on fluid flow characterized as Newtonian, incompressible, and steady. The mathematical formulation is derived from the Navier--Stokes equations, discretized using the Finite Volume Method (FVM) and solved through the Semi-Implicit Method for Pressure-Linked Equations (SIMPLE) algorithm. Numerical simulations are performed in MATLAB with variations in stenosis length. The results demonstrate how different geometric shapes and stenosis lengths affect blood flow rate and pressure distribution. Among all configurations, the Bell--Cosine geometry consistently produces a flow rate above the normal threshold and a pressure level below the normal range for each stenosis length ($40\,μ\text{m}$, $50\,μ\text{m}$, $60\,μ\text{m}$, $70\,μ\text{m}$), compared with the other geometries. For every geometric arrangement, stenosis length plays a role in altering the flow behavior and pressure field around the constriction, while the peak velocity and peak pressure remain essentially unchanged.